2023
DOI: 10.3390/land12020355
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Climate and Land Cover Change over West Africa

Abstract: Climate–land interaction over West Africa has often been assessed using climate simulations, although the model-based approach suffers from the limitations of climate models for the region. In this paper, an alternative method based on the analysis of historical land cover data and standardized climatic indices is used to investigate climate–land interactions, in order to establish climatic conditions and their corresponding land cover area changes. The annual variation in land cover area changes and climatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, an increase in the number of extreme rainfall days in West Africa has been projected especially in its Sahelian part (Vizy & Cook, 2012), with more intense and frequent occurrences of extreme rainfall over the Guinea highlands and Cameroon mountains (Haensler et al, 2013; Sylla et al, 2012). However, from 1975 to 2019, the natural landscape of the West African biogeographic region has been progressively replaced by an anthropogenic landscape dominated by agriculture (Barnieh et al, 2020; Dimobé et al, 2015; Gansaonré, 2018; Mortey et al, 2023). Thus, due to the predicted increase in humidity, the loss of the large part of the Sudanian and Guinean forests which are replaced by savannah zones (Mortey et al, 2023), and the results shown by Figure 5b–e, the future climate is likely to become more suitable for P. bibroni .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, an increase in the number of extreme rainfall days in West Africa has been projected especially in its Sahelian part (Vizy & Cook, 2012), with more intense and frequent occurrences of extreme rainfall over the Guinea highlands and Cameroon mountains (Haensler et al, 2013; Sylla et al, 2012). However, from 1975 to 2019, the natural landscape of the West African biogeographic region has been progressively replaced by an anthropogenic landscape dominated by agriculture (Barnieh et al, 2020; Dimobé et al, 2015; Gansaonré, 2018; Mortey et al, 2023). Thus, due to the predicted increase in humidity, the loss of the large part of the Sudanian and Guinean forests which are replaced by savannah zones (Mortey et al, 2023), and the results shown by Figure 5b–e, the future climate is likely to become more suitable for P. bibroni .…”
Section: Discussionmentioning
confidence: 99%
“…However, from 1975 to 2019, the natural landscape of the West African biogeographic region has been progressively replaced by an anthropogenic landscape dominated by agriculture (Barnieh et al, 2020; Dimobé et al, 2015; Gansaonré, 2018; Mortey et al, 2023). Thus, due to the predicted increase in humidity, the loss of the large part of the Sudanian and Guinean forests which are replaced by savannah zones (Mortey et al, 2023), and the results shown by Figure 5b–e, the future climate is likely to become more suitable for P. bibroni . The increasing favourable habitats of P. bibroni in the future could also be explained by the fact that this species prefers savannah shrub‐land and grassland to forest habitats (Amphibiaweb, 2023; Rödel, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations